Feebly lifting modules - Cihat Abdioğlu; Esra Özturk Sozen (Journal of Mahani Mathematical Research)
In this article feebly lifting modules are defined. A module $W$ is called feebly lifting provided, for each fully idempotent $N≤ W$ there exists a direct summand $D≤ W$ providing $D≤ N$ and $\frac{N}{D}\ll \frac{W}{D}$. The basic properties and ring characterizations of these modules are investigated.